La selección modal en las cláusulas adverbiales introducidas por como si - Nowikow, Wiaczesław (Studia Romanica Posnaniensia, 2019)
The conjunction como si select usually in the subordinated adverbial clauses (modal, conditional and comparative) the tenses of the subjunctive mood cantara / cantase and hubiera / hubiese cantado. However in some papers is mentioned the possibility of the construction of como si with the tenses of indicative mood. This paper contains the analysis of the modal selection after como si and, particularly, the possible substitution of subjunctive by the indicative tenses. The analyses is realized on the ground of the corpus of Real Academia Española (CORPES XXI, CREA, CREA. Versión anotada).